Histamine Potentiates SARS-CoV-2 Spike Protein Entry Into Endothelial Cells - Raghavan, Somasundaram; Leo, M. Dennis (Frontiers in Pharmacology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which causes coronavirus disease (COVID-19) is one of the most serious global health crises in recent history. COVID-19 patient symptoms range from life-threatening to mild and asymptomatic, which presents unique problems in identifying, quarantining, and treating affected individuals. The emergence of unusual symptoms amongst survivors, now referred to as ‘Long COVID’, is concerning, especially since much about the condition and the treatment of it is still relatively unknown. Evidence so far also suggests that some of these symptoms can be attributed to vascular inflammation. Although famotidine, the commonly used histamine H2 receptor (H2R) blocker, was shown to have no antiviral activity, recent reports indicate that it could prevent adverse outcomes in COVID-19 patients. Histamine is a classic pro-inflammatory mediator, the levels of which increase along with other cytokines during COVID-19 infection. Histamine activates H2R signaling, while famotidine specifically blocks H2R activation. Investigating the effects of recombinant SARS-CoV-2 spike protein S1 Receptor-Binding Domain (Spike) on ACE2 expression in cultured human coronary artery endothelial cells, we found that the presence of histamine potentiated spike mediated ACE2 internalization into endothelial cells. This effect was blocked by famotidine, protein kinase A inhibition, or by H2 receptor protein knockdown. Together these results indicate that histamine and histamine receptor signaling is likely essential for spike protein to induce ACE2 internalization in endothelial cells and cause endothelial dysfunction and that this effect can be blocked by the H2R blocker, famotidine.